Molecular diagnosis of Groundnut bud necrosis virus causing bud blight of tomato - R.K. JAIN*, P. RAJA and (Indian Phytopathology, 2006)
Bud blight affected tomato samples collected from Coimbatore (Tamil Nadu : TN-Co), Kanpur (Uttar Pradesh : UP-Ka), Pune (Maharashtra :MH-Pu) and Rahuri (Maharashtra : MH-Ra) showed positive reaction with polyclonal antiserum to nucleocapsid protein (N) of Groundnut bud necrosis virus (GBNV) in direct antigen- coated enzyme-linked immunosorbent (DAC-ELISA) and dot immunobinding (DIBA) assays, suggesting the association of a Tospovirus antigenically related to GBNV. The virus was detected both in leaf tissues and fruit pericarp. Tomato Tospovirus isolates (TN-Co, UP-Ka, MH-Pu and MH-Ra) were mechanically transmitted to cowpea (Vigna unguiculata cv. Pusa Komal), a diagnostic assay host for Tospovirus. The nucleocapsid protein gene could be amplified using GBNV specific primers from both leaf and fruit pericarp tissues from bud blight affected plants. The amplicons were specific and reproducible, confirming the association of GBNV with bud blight affected samples collected from four locations.